USAHA PENGEMBANGAN TERNAK SAPI UNTUK KESEJAHTERAAN MASYARAKAT DESA KALIJAGA SELATAN KECAMATAN AIKMEL KABUPATEN LOMBOK TIMUR DI TINJAU DARI PERSFEKTIF EKONOMI ISLAM - Itriyah, Siti; Irwan, Muhammad (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
The purpose of this research is to find out the mechanism of the profit-sharing system of cattle business carried out by the people of Kalijaga Selatan Village. Whether this form of profit-sharing cooperation can prosper the community and is in accordance with the perspective of Islamic economics. The research approach used in this study is qualitative research with descriptive methods, with data collection techniques of interviews, observation and documentation.The results showed that the cattle development business carried out by the people of Kalijaga Selatan Village, Aikmel Subdistrict is a mudharabah profit-sharing practice when viewed from Islamic Economics, namely capital management cooperation by capital owners (sahibul mal) and managers (mudharib) in exchange for 50:50 profit sharing according to the agreement of both parties at the beginning of the collaboration. This cooperation for the production of cattle turned out to have a very positive impact on the people of Kalijaga Selatan Village, where since this cooperation the manager and owner have been greatly helped, especially to fulfill their daily needs, send their children to college and even be able to go on pilgrimage. Keywords: Profit Sharing, Mudharabah, Cattle Farming